CULTURALLY RESPONSIVE PEDAGOGY: ADAPTING INSTRUCTION TO DIVERSE STUDENT POPULATIONS - Rahmonqulova Kamola Muzaffar qizi (TADQIQOTLAR.UZ, 2024)
Abstract: This article explores the principles and practices of culturally responsive pedagogy, an approach that seeks to create inclusive and equitable learning environments by acknowledging, validating, and leveraging the diverse cultural backgrounds, experiences, and ways of knowing that students bring to the classroom. It examines how educators can implement culturally responsive teaching methods to better meet the academic and socio-emotional needs of students from diverse racial, ethnic, linguistic, and socioeconomic backgrounds. The article highlights evidence- based strategies for curriculum design, instructional delivery, student-teacher relationships, and classroom climate that promote cultural responsiveness and empower all learners to thrive.